2014
DOI: 10.1007/s10616-014-9700-9
|View full text |Cite
|
Sign up to set email alerts
|

Freshly frozen E18 rat cortical cells can generate functional neural networks after standard cryopreservation and thawing procedures

Abstract: Primary dissociated brain tissue from rodents is widely used in a variety of different scientific methods to investigate cellular processes in vitro. Often, for this purpose cell cultures need to be generated just on time, requiring extensive animal lab infrastructure. We show here that cryopreservation and thawing of dissociated tissue from rat cerebral cortex at embryonic day 18 is feasible without affecting its ability to form functional neuronal networks in vitro. Vitality of fresh and re-thawed cortical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Using whole-cell patch clamp electrophysiology, we observed similar examples of spontaneous and evoked APs elicited by fresh and cryostored neurons, in agreement with previous reports that the number, burst duration, and amplitude of APs are not significantly affected following cryostorage in several media ( Otto et al, 2003 ; Quasthoff et al, 2014 ; Pischedda et al, 2018 ). Additionally, careful analysis of specific features of evoked AP waveforms did not detect significant differences after recovery from cryostorage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using whole-cell patch clamp electrophysiology, we observed similar examples of spontaneous and evoked APs elicited by fresh and cryostored neurons, in agreement with previous reports that the number, burst duration, and amplitude of APs are not significantly affected following cryostorage in several media ( Otto et al, 2003 ; Quasthoff et al, 2014 ; Pischedda et al, 2018 ). Additionally, careful analysis of specific features of evoked AP waveforms did not detect significant differences after recovery from cryostorage.…”
Section: Discussionsupporting
confidence: 90%
“…Despite these benefits, the adoption of neuronal cryopreservation methods has been limited ( Paynter, 2008 ). Pioneering studies found that neuronal cells could be frozen in “hibernation media” supplemented with cryoprotectant, which on revival yielded neurons that appeared morphologically and physiologically normal ( Kawamoto and Barrett, 1986 ; Mattson and Kater, 1988 ; Petite and Calvet, 1995 ; Otto et al, 2003 ; Quasthoff et al, 2014 ). However, despite optimization of freezing parameters and media composition, the viability and long-term survival of cryostored neurons was consistently low using these methods ( Higgins et al, 2011 ; Robert et al, 2016 ), rendering neuronal cryopreservation an inefficient practice.…”
Section: Introductionmentioning
confidence: 99%
“…Neurostore contains a proprietary combination of cryoprotective agents to reach a superior viability of primary cultures upon thawing. Other studies have proposed protocols to achieve a satisfactory cryopreservation of neural cells (Das et al, 1983 ; Fang and Zhang, 1992 ; Negishi et al, 2002 ; Higgins et al, 2011 ; Quasthoff et al, 2015 ; Robert et al, 2016 ). However, previously published studies measured mainly qualitative outcome of viability (Das et al, 1983 ; Fang and Zhang, 1992 ; Robert et al, 2016 ) or cell membrane integrity (Negishi et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few authors characterized cryopreserved cultures in deeper detail. For example, Higgins et al ( 2011 ) provided a qualitative evaluation of neuritic tree formation and only Quasthoff et al ( 2015 ) included a parametric analysis of morphological and functional development of the cultures. In our study, we found no major differences in the viability of the fresh and frozen cells at different time points of their maturation.…”
Section: Discussionmentioning
confidence: 99%
“…While there are membrane potential measurements that can only be carried out in single cells, assessment of neuronal populations can be highly informative as well. Multi‐electrode arrays (MEAs) allow recording of the electrical activity of neuronal networks grown on multiple extracellular electrodes (Berdondini et al, ; Chiappalone, Bove, Vato, Tedesco, & Martinoia, ; Illes, Theiss, Hartung, Siebler, & Dihné, ; Novellino et al, ; Otto, Go, Fleischer, & Siebler, ; Quasthoff et al, ; Schock et al, ). The advantages of this technology are its relative simplicity, compactness and ease of monitoring, as well as its potential for high throughput (Hales, Rolston, & Potter, ; Pine, ; Spira & Hai, ).…”
Section: Introductionmentioning
confidence: 99%